Βιβλιοκρισία:Eustathios of Thessaloniki, Secular Orations 1167/8 to 1179, translated by Andrew F. STONE, with an introduction and commentary [Byzantina Australiensia 19], Brisbane 2013, σελ. xxv+241. ISBN: 978-1-876503-36-9 - ΜΕΡΙΑΝΟΣ Γεράσιμος (Byzantina Symmeikta, 2016)
Βιβλιοκρισία: Eustathios of Thessaloniki, Secular Orations 1167/8 to 1179, translated by Andrew F. Stone, with an introduction and commentary [Byzantina Australiensia 19], Brisbane 2013, σελ. xxv+241. ISBN: 978-1-876503-36-9